Indication, Timing, and Surgical Treatment of Spontaneous Intracerebral Hemorrhage: Systematic Review and Proposal of a Management Algorithm - Luzzi, Sabino; Elia, Angela; Del Maestro, Mattia; Morotti, Andrea; Elbabaa, Samer K.; Cavallini, Anna; Galzio, Renato (World neurosurgery, 2019)
To delineate the most recommendable treatment of spontaneous intracerebral hemorrhages and the indication for surgery, its timing, and the best surgical technique to be adopted case by case. Based on PubMed/MEDLINE, Embase, and the Cochrane Library databases, a systematic review of the literature was performed using as keywords the terms "spontaneous intracerebral hemorrhage," "surgical management," "medical management," "supratentorial," and "infratentorial." Because of the highest level of evidence, only randomized and nonrandomized clinical trials, meta-analyses, and comparative cohort studies reported within the last 12 years were selected. An updated and evidence-based treatment algorithm was reported also. The search initially returned 255 articles. After application of the exclusion criteria, only 19 studies were selected. According to the site and volume of the hematoma, admission Glasgow Coma Scale (GCS) score, and progressive neurologic decline, specific subgroups were identified. Surgery must be considered in patients with an admission GCS score ranging between 5 and 12 and a hematoma volume >30 mL. The best time-window has been reported to be 7–24 hours after ictus. Endoscopic surgery is recommendable for patients with a supratentorial hematoma >60 mL and with a poor GCS score (4–8). Alternative techniques, such as minimally invasive puncture and thrombolysis, may be considered for deeper hematoma. Careful selection of patients eligible for surgery is mandatory. The optimal timing falls into a time-window ranging between 7 and 24 hours after ictus. Minimal invasive techniques are valuable surgical options for patients in a poor GCS score or harboring large deep-seated hemorrhages.